Applicability of formulas for calculating differential renal depth - Luo Jin; Deng Wei; Cao Jiang; Tian Jia-li; Wang Ying; Wang Rong; Li Yan-mei; Zhao Qian; Yang Ji-qin; Li Juan (Linchuang shenzangbing zazhi)
Objective To evaluate the applicability of differential renal depth calculation formulas for Chinese people and provide references for selecting renal depth calculation formulas.Methods The SPECT/CT data were analyzed retrospectively for 234 patients with glomerular filtration rate measured by renal dynamic imaging from May to December 2018.CT depth was measured as the standard, correlation, average difference and 1 cm error rate between six renal depth calculation formulas and CT measurements were compared.Results Strong correlations existed between estimated values of six formulas and measured values of CT.Data analysis showed that the correlation coefficient between Lee’s equation and CT measured values was better than that of the other five formulas, r=0.737 for left kidney and 0.750 for right kidney.The renal depth obtained by Lee’s equation was closest to that measured by CT and the difference was not statistically significant（left kidney mean deviation 0.03 cm, right kidney mean deviation 0.08 cm）.The 1 cm error rate of Tonnesen formula was the largest.And it was 54.70% for left kidney and 57.69% for right kidney.The 1 cm error rates of the other five formulas were tested by X2 test and there was no statistical difference（P>0.05）.Conclusions No significant difference exists between left and right kidney depth calculated by Lee’s equation and the measured value of CT.Its deviation range is small and it is better than the other five formulas.A wider clinical popularization is worthwhile.